Off-State Operation of a Three Terminal Ionic FET for Logic-in-Memory - Xiaoyao Song; Ashwani Kumar; Maria Merlyne De Souza (IEEE Journal of the Electron Devices Society, 2019)
We demonstrate a novel concept for low power compute-in-memory applications in a room temperature fabricated ZnO/Ta2O5 thin film transistor. By writing during the off-state, the device power consumption is reduced to nW despite a large L/W ratio. A thinner gate insulator thickness gives higher on/off ratio, nevertheless this reduces the retention time. The on/off ratio in the thicker oxide can be improved by asymmetric voltage pulses of higher magnitude in the off state without affecting power consumption. Benchmarked against other ReRAM devices, the device shows a competitive 8 nJ per transition, which allows a reduction in power consumption compared to a filamentary device. Such non-filamentary devices have closer similarity to biological synapses on account of slow operating speed.